Synthesis of the hexasaccharide from Trypanosoma cruzi mucins with the Galp(1 → 2)Galf unit constructed with a superarmed thiogalactopyranosyl donor - Kashiwagi, Gustavo Adolfo (2019)
Hexasaccharide β-D-Galp-(1→ 2)-[β-D-Galp-(1 → 3)]-β-D-Galp-(1 → 6)-[β-D-Galp-(1 → 2)-β-D-Galf-(1 → 4)]-D-GlcNAc (1) was found O-linked in mucins of Trypanosoma cruzi epimastigotes and metacyclic trypomatigotes. Studies on the biological pathways and functionalities of the mucin oligosaccharides are prompted in order to understand the interactions of these molecules with the insect host. Trisaccharide constituent β-D-Galp-(1 → 2)-β-D-Galf-(1 → 4)-D-GlcNAc was constructed from the reducing to the non-reducing end. We discuss the difficulties to introduce a Galp unit at the O-2 position of a partially protected galactofuranosyl unit which were overcome using an anchimerically superarmed donor. By this route and employing a [3 + 3] nitrilium convergent approach hexasaccharide 1 was synthesized in moderate yield.